2020
DOI: 10.1039/d0ob00240b
|View full text |Cite
|
Sign up to set email alerts
|

Reagent controlled stereoselective synthesis of teichoic acid α-(1,2)-glucans

Abstract: Additive controlled glycosylation reactions are used for the construction of α-(1,2)-glucosidic linkages, such as those featuring in E. faecalis lipoteichoic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…DMF-mediated glycosylations permitted access to long structures based on multiple α(1–4) linkages 33 and 34 [ 178 ] and α(1–3) linkages 35 [ 179 ] ( Scheme 5B ). The short oligosaccharide 36 having α(1–2) linkages was also prepared, however, in this case, the stereoselectivity diminished with the increasing length of the oligosaccharide, possibly due to steric hindrance [ 180 ].…”
Section: Reviewmentioning
confidence: 99%
“…DMF-mediated glycosylations permitted access to long structures based on multiple α(1–4) linkages 33 and 34 [ 178 ] and α(1–3) linkages 35 [ 179 ] ( Scheme 5B ). The short oligosaccharide 36 having α(1–2) linkages was also prepared, however, in this case, the stereoselectivity diminished with the increasing length of the oligosaccharide, possibly due to steric hindrance [ 180 ].…”
Section: Reviewmentioning
confidence: 99%
“…The antigenic heterogeneity of LTA necessitates structure-activity studies for the elucidation of the immunogenic epitopes. In this case, synthetic groups of LTA, i.e., the D-alanine kojibiose functionalized LTA from E. faecalis, and TA fragments would be useful tools [85,86]. In an attempt to develop a vaccine candidate targeting LTA by synthetic approaches, Laverde et al identified a synthetic teichoic acid, WH7, able to absorb the opsonic activity of antibodies raised against enterococcal LTA.…”
Section: Enterococcal Proteinsmentioning
confidence: 99%